Aboveground litter addition for five years changes the chemical composition of soil organic matter in a temperate deciduous forest. (October 2021) - Wang, Xin; Dai, Weiwei; Filley, Timothy R.; Wang, Chao; Bai, Edith
Abstract: Global climate change has been found to affect plant net primary production and thereby could modify the quantity and quality of aboveground litter, which may consequently affect soil organic carbon (SOC). Whether those changes have influenced the chemical components of SOC is still unclear, especially for the soil beneath the surface soil. This study examined the changes in biopolymers (lignin, substituted fatty acids, amino sugars) in 0–10 cm and 10–20 cm soil depth in a temperate forest after five years of aboveground litter addition or removal treatments. The results showed that although SOC and soil nitrogen contents were not influenced by litter manipulation, the lignin phenols and substituted fatty acids contents in SOC of 10–20 cm soil were significantly higher in litter addition treatment compared to litter removal treatment, suggesting a selective accumulation pathway for these plant biopolymers in the 10–20 cm soil under litter manipulation. Soil amino sugar content, however, was not influenced by litter manipulation, although microbial biomass carbon (MBC) and nitrogen in 0–10 cm soil were significantly higher in litter addition plots due to the significantly higher substrate availability (dissolved organic carbon) and nutrient availability (total dissolved nitrogen) than those in the control. Although higher MBC could increase decomposition of SOC, this effect did not counterbalance the effect of higher aboveground litter input in litter addition plots, but rather changed the composition of SOC toward compounds of a purportedly more stable composition. The effects of aboveground litter removal were not entirely in contrast to the effects of aboveground litter addition on SOC, hinting that belowground inputs could sustain the storage of SOC for at least five years under aboveground litter removal treatment. The changes in the chemical composition of SOC under litter manipulation for five years suggested the potential changes in SOC stability and pool size in the future, especially in the 10–20 cm soil, to which more attention should be paid in future litter manipulation studies. Highlights: Litter addition increased lignin phenols and substituted fatty acids contents in SOC (10–20 cm). Soil amino sugar content was not influenced by litter manipulation. Litter addition increased soil DOC and TDN and therefore increased microbial biomass carbon. The effects of aboveground litter removal were not entirely contrary to those of litter addition.